A New Method for In Vivo Analysis of the Performances of a Heat and Moisture Exchanger (HME) in Mechanically Ventilated Patients - Filippini, Matteo; Serpelloni, Mauro; Quaranta, Valeria; Bellitti, Paolo; Sardini, Emilio; Latronico, Nicola (Pulmonary Medicine, 2019)
Aim. To evaluate the conditioning capabilities of the DAR™ Hygrobac™ S, a Heat and Moisture Exchanger (HME), using a new device to measure the temperature (T) and the absolute humidity (AH) of the ventilated gases in vivo during mechanical ventilation in Intensive Care Unit (ICU) patients. Materials and Methods. In 49 mechanically ventilated ICU patients, we evaluated T and AH, indicating the HME efficacy, during the inspiratory phase upstream and downstream the HME and the ratio of inspired AH to expired AH and the difference between expired T and inspired T indicated the HME efficiency. Efficacy and efficiency were assessed at three time points: at baseline (t0, HME positioning time), at 12 hours (t1), and at 24 hours (t2) using a dedicated, ad hoc built wireless device. Differences over time were evaluated using one-way ANOVA for repeated measures, whereas differences between in vivo and laboratory values (declared by the manufacturer according to UNI® EN ISO 9360 international standard) were evaluated using one-sample Student t-test. Results. 49 HMEs were analysed in vivo during mechanical ventilation. T and AH means (SD) of the inspired gas (the efficacy) were 31.5°C (1.54) and 32.3 mg/l (2.60) at t0, 31.1°C (1.34) and 31.7 mg/l (2.26) at t1, and 31°C (1.29) and 31.4 mg/l (2.27) at t2. Both efficiency parameters were constant over time (inspired AH/expired AH=89%, p=0.24; and expired T–inspired T = 2.2°C, p=0.81). Compared with laboratory values, in vivo T and AH indicating efficacy were significantly lower (p<0.01), whereas the efficiency was significantly higher (p<0.01). Conclusions. HME performances can be accurately assessed for prolonged periods in vivo during routine mechanical ventilation in ICU patients. Temperature and absolute humidity of ventilated gases in vivo were maintained within the expected range and remained stable over time. HME efficacy and efficiency in vivo significantly differed from laboratory values.